Processing of high performance composites based on peek by aqueous suspension prepregging - Nohara, Liliana Burakowski [UNESP] (2010)
The use of polyamic acid (PAA) precursor as interphase in polymer composites is one of the many applications of polyimides (PIs). In this work, composites based on poly(ether-ether-ketone) (PEEK) and carbon fibers were prepared using two manufacturing techniques for thermoplastic composites: hot compression molding, and aqueous polymeric suspension prepregging using PIs as interphase. Two PAAs were synthesized and used as interphases: 3,3'-4,4'-benzophenonetetracarboxylic dianhydride/oxydianiline (BTDA/ODA) and pyromellitic dianhydride/oxydianiline (PMDA/ODA). The PAA/PI systems were analyzed by differential scanning calorimetry (DSC), thermogravimetry (TGA), Fourier transform infrared spectroscopy (FTIR) and nuclear magnetic resonance (NMR). Results from these analyses confirmed the synthesis of these compounds. Aqueous polymeric suspension prepregging was more efficient than hot compression molding when the PMDA/ODA PAA/PI interphase was used; also, the interlaminar shear strength of composites produced using this technique was 14.5% higher than the one produced using hot compression molding.